ST2 and CSF‐1 as potential druggable targets of inflammatory bowel diseases: Results from two‐sample Mendelian randomization study - Jiarui Mi; Xia Wu; Xiaoyin Bai; Yang Yang; Hong Yang (Wiley, 2023)
Abstract Novel druggable targets are warranted for inflammatory bowel disease (IBD) treatment. We aimed to identify novel circulating proteins with causal associations with the risk of IBDs and provide potential therapeutic targets for IBD treatment. We performed a two‐sample Mendelian randomization (MR) study to explore the associations of 55 circulating biomarkers on the risk of IBD, Crohn's disease (CD), and ulcerative colitis (UC) by leveraging the summary statistics from large genomewide association studies and protein quantitative trait loci studies. The individual estimate was pooled together by meta‐analyses to estimate the causal effects of each outcome. In univariable MR, we identified several circulating proteins showed potential correlation with IBD, UC, and CD. Of note, we observed that a genetically proxied increased level of suppression of tumorigenicity 2 (ST2) was associated with an elevated risk of IBD (odds ratios [ORs] 1.133, 95% confidence interval [CI] 1.091-1.176, p < 0.0001), CD (ORs 1.188, 95% CI 1.103-1.281, p < 0.0001), and UC cohorts (ORs 1.087, 95% CI 1.050-1.125, p < 0.0001). Additionally, we observed a consistent positive correlation between the level of CSF‐1 and the increased risk of IBD in individual MR, with statistically significant causal associations in the meta‐analyses with ORs equal to 1.217 (IBD, 95% CI 1.115-1.328, p < 0.0001), 1.223 (CD, 95% CI 1.082-1.382, p = 0.0013), and 1.179 (UC, 95% CI 1.055-1.317, p = 0.0037). This study provided evidence for potential casual associations between circulating ST2 and CSF‐1 levels, and increased risks of IBD, UC, and CD, implicating potential treatment targets for IBD and subtypes.